The COVID-19 Shock and Equity Shortfall: Firm-Level Evidence from Italy - Carletti, Elena; Oliviero, Tommaso; Pagano, Marco; Pelizzon, Loriana; Subrahmanyam, Marti G (The Review of Corporate Finance Studies, 2020)
We employ a representative sample of 80,972 Italian firms to forecast the drop in profits and the equity shortfall triggered by the COVID-19 lockdown. A 3-month lockdown generates an aggregate yearly drop in profits of about 10% of GDP, and 17% of sample firms, which employ 8.8% of the sample's employees, become financially distressed. Distress is more frequent for small and medium-sized enterprises, for firms with high pre-COVID-19 leverage, and for firms belonging to the Manufacturing and Wholesale Trading sectors. Listed companies are less likely to enter distress, whereas the correlation between distress rates and family firm ownership is unclear.